Wyjątki z domu Ludwisi - Rączka, Teresa (Postscriptum Polonistyczne, 2020)
The author reads Adam Mickiewicz’s [Urywek Pamiętnika Polki] in the context of symbolic space of a house “from the basement to the attic” suggested by Gaston Bachelard. Fenomenological doubts of French critic provoke questions concerning “beloved space” and “shelter” in Mickiewicz’s text. Deconstrucion that leads to accepting Ludwisia’s perspective reveals vertical dimension of the house and enables to designate places for figures living there. The most important belongs to a modest servant girl.